Current trends in the treatment of polycystic ovary syndrome with desire for children - Margalida E Sastre; Maria O Prat; Miguel Angel Checa; Ramon C Carreras (Dove Medical Press, 2009)
Margalida E Sastre1, Maria O Prat1, Miguel Angel Checa1,2, Ramon C Carreras11Department of Obstetrics and Gynaecology; 2Unit of Endocrinological Gynaecology and Human Reproduction, Hospital del Mar, Autonomous University of Barcelona, Barcelona, SpainAbstract: Polycystic ovary syndrome (PCOS), one of the most frequent endocrine diseases, affects approximately 5%–10% of women of childbearing age and constitutes the most common cause of female sterility regardless of the need or not for treatment, a change in lifestyle is essential for the treatment to work and ovulation to be restored. Obesity is the principal reason for modifying lifestyle since its reduction improves ovulation and the capacity for pregnancy and lowers the risk of miscarriage and later complications that may occur during pregnancy (gestational diabetes, pre-eclampsia, etc). When lifestyle modification is not sufficient, the first step in ovulation induction is clomiphene citrate. The second-step recommendation is either exogenous gonadotrophins or laparoscopic ovarian surgery. Recommended third-line treatment is in vitro fertilization. Metformin use in PCOS should be restricted to women with glucose intolerance.Keywords: polycystic ovarian syndrome, clomiphene citrate, letrozole, lifestyle, pregnancy, obesity